Placental pathology in perinatal asphyxia: a case–control study - Alongi, Silvia; Lambicchi, Laura; Moltrasio, Francesca; Botto, Valentina Alice; Bernasconi, Davide Paolo; Cuttin, Maria Serena; Paterlini, Giuseppe; Malguzzi, Silvia; Locatelli, Anna (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction Placentas of term infants with birth asphyxia are reported to have more lesion such as maternal vascular malperfusion (MVM), fetal vascular malperfusion (FVM) and chorioamnionitis with fetal response (FIR) than those of term infants without birth asphyxia. We compared the placental pathology of asphyxiated newborns, including those who developed hypoxic-ischemic encephalopathy (HIE), with non-asphyxiated controls. Methods We conducted a retrospective case–control study of placentas from neonates with a gestational age ≥ 35 weeks, a birthweight ≥ 1,800 g, and no malformations. Cases were asphyxiated newborns (defined as those with an umbilical artery pH ≤ 7.0 or base excess ≤ −12 mMol, 10-minute Apgar score ≤ 5, or the need for resuscitation lasting >10 min) from a previous cohort, with (n=32) and without (n=173) diagnosis of HIE. Controls were non-asphyxiated newborns from low-risk l (n= 50) or high-risk (n= 68) pregnancies. Placentas were analyzed according to the Amsterdam Placental Workshop Group Consensus Statement 2014. Results Cases had a higher prevalence of nulliparity, BMI>25, thick meconium, abnormal fetal heart monitoring, and acute intrapartum events than controls (p<0.001). MVM and FVM were more frequent among non-asphyxiated than asphyxiated newborns (p<0.001). There was no significant difference in inflammatory lesions or abnormal umbilical insertion site. Histologic meconium-associated changes (MAC) were observed in asphyxiated newborns only (p= 0.039). Discussion Our results confirm the role of antepartum and intrapartum risk factors in neonatal asphyxia and HIE. No association between neonatal asphyxia and placental lesions was found, except for in the case of MAC. The association between clinical and placental data is crucial to understanding and possibly preventing perinatal asphyxia in subsequent pregnancies.